Adesmia subtropicalis (Leguminosae, Papilionoideae, Dalbergieae), a new endangered species from the Brazilian Pampas - Monteiro, Thiago Cobra E; Iganci, João Ricardo Vieira; Miotto, Silvia T.s.; Fortuna-Perez, Ana Paula (Phytotaxa, 2021)
In the context of an ongoing taxonomic review of Adesmia subg. Adesmia ser. Bicolores, a new endangered species endemic to Rio Grande do Sul state, Brazil, is herein described. The new species present a long glandular ochraceous indumentum, flowers 10–15 mm long, and arilated seeds. Information about morphology, differences from closely related species, phenology, conservation status, and etymology are provided.